Effect of Bio Energy Power Exercise on VO2max and Heart Rate - Yudhi Nugroho, Chris Tomy; Sulistiono, Sulistiono; Mashuri, Hendra; Amin, Mohamad (UNIVERSITAS NEGERI MAKASSAR, 2021)
The purpose of this study was to determine the effect of bio energy power exercise on vo2max and heart rate, this study used a quantitative approach, the type of quasi-experimental research, the subjects are taken in this study were male students who took futsal extracurricular activities aged 10-12 years, to find out Vo2max using the 1600 meter run test and to determine the heart rate score using the Harvard test, data analysis is in the form of descriptive analysis and simple regression. The results showed that the use of bio energy power training did not provide a significant change in VO2max and did not provide a significant increase in the heart rate score with the length of the study for 5 meetings, but there was an increase in the VO2max value in the first week to the last week which means that the increase was not significant, and there was a gradual increase in the heart rate score starting from exercise in the first week to the last week, which means an increase although not significant.